New Larousse encyclopedia of mythology - Introduction by Robert Graves [translated from the French by Richard Aldington and Delano Ames, and revised by a panel of editorial advisors from the Larousse mythologie générale edited by Felix Guirand]. (Hamlyn, 1968)
First ed. published in 1959 under title: Larousse encyclopedia of mythology.